Abdominal subcutaneous fat thickness combined with a 50-g glucose challenge test at 24-28 weeks of pregnancy in predicting gestational diabetes mellitus - Süleyman Cemil Oğlak; Emine Zeynep Yılmaz; Mehmet Şükrü Budak (Taylor & Francis Group, 2024)
Background This investigation aimed to analyse the efficacy of abdominal subcutaneous fat thickness (ASFT) value >18.1 mm combined with a 50-g glucose challenge test (GCT) between 24-28 weeks of gestation in predicting gestational diabetes mellitus (GDM) cases.Methods This cross-sectional study was carried out from February 2021 to December 2022. All pregnant women received a 50-g GCT at 24-28 weeks of pregnancy for the GDM screening. Pregnant women with a blood glucose value between 140-190 mg/dl experienced 100 g OGTT. Even if 50-g GCT was normal, 100-g OGTT was offered to patients with an ASFT value above 18.1 mmResults Among the 728 pregnant women we enrolled, 154 (21.2%) cases were screened as positive. The number of patients who first screened positive and determined to be GDM after the 100-g oral glucose tolerance test (OGTT) was 43 (5.9%). A total of 67 cases (9.2%) had an ASFT measurement above 18.1 mm. Two cases with a negative 50-g GCT and ASFT <18.1 mm were diagnosed as GDM in the later weeks of pregnancy. A 50-g GCT combined with ASFT measurement above 18.1 mm predicted GDM with a sensitivity of 87.9%, a specificity of 88.7%, a positive predictive value (PPV) of 36.0%, and a negative PV (NPV) of 99.7%.Conclusions A 50-g GCT combined with ASFT measurement that can be easily and accurately obtained during routine antenatal care in the second trimester might be a beneficial indicator for predicting GDM cases.